Investigation on Sb-doped induced Cu(InGa)Se2 films grain growth by sputtering process with Se-free annealing. (15th November 2017) - Zhang, Leng; Zhuang, Daming; Zhao, Ming; Gong, Qianming; Ouyang, Liangqi; Guo, Li; Sun, Rujun; Wei, Yaowei; Zhan, Shilu; Lyu, Xunyan; Peng, Xiao
Highlights: The incorporation of Sb2 S3 could significantly increase the CIGS grain size processed by Se-free annealing. Sb2 Se3 is generated from Sb2 S3 and decomposed into volatile phases which enhance grain growth. The highest device efficiency of 11.9% is obtained with Sb2 S3 incorporation. Abstract: In this study, the influences of doping with antimony sulfide (Sb2 S3 ) and metallic Sb on the properties of Cu(InGa)Se2 (CIGS) films and devices have been investigated. The incorporation of metallic Sb in CIGS films has little effect on grain growth, while the incorporation of Sb2 S3 could significantly increase CIGS grain size and alter the preferential orientation of CIGS films. Photoluminescence spectra reveal that the pre-deposited Sb2 S3 is beneficial to reduce or passivate defects in CIGS layer. Furthermore, the effects of annealing temperature on grain size and phase structure of Sb-doped CIGS films have been explored and Sb distribution profiles in CIGS film are elucidated. These results suggest that Sb2 S3 could take effects on enhancing grain growth beyond a certain critical temperature when the generated antimony selenide (Sb2 Se3 ), rather than Sb2 S3, decomposed into some volatile phases. These volatile phases could facilitate the diffusion of the atoms in grain boundaries when they pass through from the bottom to outside of CIGS films. Finally, the efficiency of solar cells increases from 8.4% for un-doped sample to 11.9% for Sb2 S3 -doped sample. This study provides a new approach for fabricating CIGS thin film with large grains and a potential way for non-hazardous mass production application.